Expanding policy for biodegradable plastic products and market dynamics of bio-based plastics: challenges and opportunities - Moshood, Taofeeq D.; Nawanir, Gusman; Fatimah, Mahmud; Fazeeda, Mohamad; Mohd Hanafiah, Ahmad; Airin, Abdul Ghani (MDPI, 2021)
Abstract: Bio-plastics are rapidly growing in popularity, and many new techniques and approaches are emerging as a result of intensive research and development (R&D) activities. Many industries worldwide are installing their new production capability. Bio-plastics have attracted political leaders’ interest, especially in light of the evolving bio-economic orientation, through their use of renewable resources and their effects on sustainable growth. Related market determinants are defined, classified, and used as a base for their own estimates. The evolution of global production capacity is modeled annually for the timeframe up to 2030 by applying a system dynamics strategy. For a long-term forecast to catch the inherent volatility, various scenarios are identified and added to the model to represent different trends in the price of gross domestic product (GDP), oil, and bioplastic feedstock. Thus, our findings show the sensitivity in the macro-economic climate of the bioplastics sector. The simulations are completed by a debate on the regulatory environment and its future effect on industry development at the European level. The findings show considerable potential for development but are vulnerable to political and economic impacts.